The Marfan syndrome gene locus as a favoured locus for susceptibility to schizophrenia. - Kalsi, G; Mankoo, BS; Brynjolfsson, J; Curtis, D; Read, T; Murphy, P; Sharma, T; Petursson, H; Gurling, HM (1994)
Marfan syndrome (MS) is a rare autosomal dominant disorder of connective tissue with manifestations in the cardiovascular, ocular and skeletal systems. Genetic linkage analysis with random probes has mapped the MS locus to 15q21.1. There have been several reports of Marfan syndrome co-segregating with schizophrenia within families, which suggest that a common genetic factor may be shared between schizophrenia susceptibility and MS. This could be due to a cytogenetic abnormality affecting both genetic loci or due to co-segregation of two disease loci near each other on the same chromosome. We tested this hypothesis by using genetic linkage analysis with multiplex families. Using three genetic markers spanning the MS locus, we were unable to find evidence of linkage with schizophrenia across the Marfan syndrome locus on chromosome 15.